The Role of Fecal Occult Blood Test in Screening of Colorectal Cancer and Inflammatory Bowel Disease - Marcellus Simadibrata (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2010)
Colorectal cancer (CRC) and inflammatory bowel disease (IBD) are a quite common colon disease in the world. The World Gastroenterology Organization (WGO) recommends screening test to detect colorectal cancer, i.e. fecal occult blood test (FOBT) and colonoscopy. Diagnosis of CRC is established based on a good history taking, clinical manifestation, physical examination and laboratory examination. Other supporting laboratory tests include routine laboratory test of hemoglobin for detecting anemia, examination of bleeding stool either macroscopically or microscopically. Radiographic examination, either colon in loop or colonoscopy (if such modalities are available), shall be performed to confirm the occurrence of cancer mass in the colon. Moreover, biopsy examination is carried out to obtain the histopathological feature of tumor mass or the type of cancers. WGO has made a guideline for CRC screening, which consists of 6 cascades, which depend on the risk of colorectal cancer and local facilities available. There are several kinds of FOBT, but the most frequently used include three methods, i.e.: the FOBT guaiac base/traditional, the fecal immunochemical test (FIT) and the FOB + transferrin rapid test (OT 102c OT 103c). FIT and FOB + transferrin rapid test have a quite high sensitivity and specificity in detecting the lower gastrointestinal tract bleeding caused by colorectal cancer and IBD. Keywords: FOBT, colorectal cancer, IBD